Efficient lipase-catalyzed synthesis of new lipid antioxidants based on a catechol structure - Torres de Pinedo, A.; Peñalver, Pablo; Rondón, Deyanira; Morales, Juan Carlos (Tetrahedron, 2005)
© 2005 Elsevier Ltd. All rights reserved. Lipid antioxidants phenolic saturated fatty acid esters were synthesized in high yields and short reaction times using the corresponding ethyl fatty acid esters, lipase from Candida Antarctica, vacuum and no solvent. Phenolic esters with mono- and polyunsaturated fatty acids (EPA and DHA) were also prepared. Peer reviewed